Analysis of Psychomotor and Biomotor Factors on Skills Field Tennis Serving Skills at the Family Tennis Club - Muh Erfan Syarif; Andi Ihsan; Hasbunallah AS; Muh Adnan Hudain; Jamaluddin Jamaluddin (Institute of Computer Science (IOCS), 2023)
The obyektive of this research is to know the effect of balance, hand eye coordination as a psychomotor factor and arm mucle strength, bacswing flexibility, leg muscle explosive power as a biomotor factor on tennis service skills at the family tenis club. This research used the correlational research. The population of this research is total 31 players at the family tenis club. The sample in this study were 31 players at the family tenis club. The data analysis technique used inferential test on regretion statistics. The results of of hypothesis testing show: 1) there is a balance effect as a significant psycomotor factor on tennis service skills at the family tenis club; 2) there is a hand eye coordination effect as a significant psycomotor factor on tennis service skills at the family tenis club 3) there is a arm muscle strength effect as a significant biomotor factor on tennis service skills at the family tenis club; 4) there is a bacswing flexibility effect as a significant biomotor factor on tennis service skills at the family tenis club; 5) there is a leg muscle explosive power effect as a significant biomotor factor on tennis service skills at the family tenis club. So from the statement above it can be concluded that 1) there is an influence of psychomotor factors on the skills of serving tennis at the family tennis club, and 2) there is an influence of biomotor factors on the skills of serving tennis at the family tennis club.